The Determinants of Children's Attainments: A Review of Methods and Findings - Haveman, Robert; Wolfe, Barbara (Journal of Economic Literature, 1995)
We review and critique the empirical literature on the links between investments in children and children's attainments. The primary theoretical perspectives that dominate this literature form the framework for our review. The potential effects on children of family choices and neighborhood characteristics are emphasized. The outcomes of interest include educational attainment, fertility choices, and work-related outcomes such as earnings and welfare recipiency. A set of tables provides details on the existing empirical literature. The focus is on the economics literature, but relevant studies from other social sciences are included as well.